79.1k views
1 vote
How do you simplify this

How do you simplify this-example-1

4 Answers

5 votes


(1-(2x)/(3x-4))/(x+(32)/(3x-4)) =((3x-4-2x)/(3x-4))/((x(3x-4)+32)/(3x-4)) =(x-4)/(3x^(2)-4x+32)

2 votes


(1-(2x)/(3x-4))/(x+(32)/(3x-4)) =((3x-4-2x)/(3x-4))/((x(3x-4)+32)/(3x-4)) =(x-4)/(3x^(2)-4x+32)

User Bilbottom
by
5.5k points
4 votes


(1-(2x)/(3x-4))/(x+(32)/(3x-4)) =((3x-4-2x)/(3x-4))/((x(3x-4)+32)/(3x-4)) =(x-4)/(3x^(2)-4x+32)

User Nick Pineda
by
6.0k points
1 vote


(1-(2x)/(3x-4))/(x+(32)/(3x-4)) =((3x-4-2x)/(3x-4))/((x(3x-4)+32)/(3x-4)) =(x-4)/(3x^(2)-4x+32)

User Rajmohan
by
5.6k points